A new endemic Begonia species (sect. Knesebeckia, Begoniaceae) from the south-western montane forest remnants of Ecuador - Pérez, Álvaro J.; Mena-Olmedo, Patricio; Cabrera, Leovigildo; León, José; Tebbitt, Mark C. (Phytotaxa, 2024)
Begonia jocotocoi is a new species described from the Buenaventura Reserve in El Oro Province, south-west Ecuador. The new species morphologically resembles Begonia serotina, but differs by its minutely bullate leaf lamina (vs. smooth), the dense red long trichomes that cover the petioles and the lower surface of the leaf lamina, the latter of which distinctly become purple at maturity (vs. usually glabrous or occasionally with an indument of minute glandular white hairs and pale green below), presence of a pair of bracteoles directly beneath the pistillate flowers (vs. bracteoles absent), and the pedicels and also sometimes the abaxial surfaces of most floral whorls having a sparse cover of glandular hairs (vs. glabrous to puberulous). Photos of the new species and a distribution map are provided. Relationships with other species are discussed and the species’ preliminary conservation status is assigned as critically endangered (CR).